THE TAXONOMY OF REGIONAL FORMS OF TERRITORIAL ORGANIZATION FOR THE NEEDS OF PLANNING OF RURAL AREAS - МальчиковаДар`я (Human Geography Journal, 2016)
In the article defined the essence of planning organization of socio-spatial systems in rural areas. It was proposed the taxonomy of the regional levels and leading forms of rural planning organization and was grounded the criteria and key features of selection of taxonomic units of geoplanning and types of operating units of geoplanning, according to the layered approach to planning at the regional level. It was expediency of allocation of geoplanning areas, geoplanning areas (functional areas) geoplanning microregions and geoplanning networks, as major taxonomic units.